Counting members in my league: Mate value moderates economic effects of local operational sex ratio - YAN, Zilin (Institutional Knowledge at Singapore Management University, 2018)
When local operational sex ratio skews toward a larger proportion of same-sex to opposite-sex individuals, should members of the surplus sex increase or decrease (economic) efforts on reproduction? Past research yielded mixed results. In light of the fact that modern humans are highly mobile and can relocate to communities that may offer better reproductive prospects, it may not always be a given that individuals facing same-sex skewed local community will become current-oriented with regard to reproduction; instead, they may contemplate whether their efforts will pay off and decide whether they prefer to wait for better situations later. The present research investigates a hitherto underexplored variable that critically underlie the now-or-later preference: mate value. Specifically, this research argues that the favorability of the context created by same-sex skewness depends on one’s mate value (and sex), and when current reproductive opportunities are perceived as acceptable (unacceptable), individuals will become current-oriented (future-oriented) in their economic choices. Study 1 reanalyzed data from a past project and found support for the moderating effect of mate value in women’s financial temporal discounting. Study 2 assessed women living in sex-skewed communities and examined their balance of reproductive and industrial goals. Study 3 further examined Singaporean students’ responses to news articles highlighting sex ratio in universities. Although many results did not achieve significance, the studies generally pinpointed that the comparison of one’s mate value to opposite-sex members and the span of sex ratio imbalance are reasonable moderators that need further scrutiny.